EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE PREDICT DISCUSS EXPLAIN OBSERVE DISCUSS EXPLAIN (PDEODE) DENGAN ASSESSMENT FOR LEARNING DAN PDEODE DENGAN PENILAIAN KONVENSIONAL PADA MATERI PELUANG DITINJAU DARI GAYA BELAJAR SISWA KELAS XII SMK - Lestari, Fajar; Mardiyana, Mardiyana; Subanti, Sri (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract. The objective of this research was to investigate the effect of the learning models on learning achievement viewed from learning style types of the students. The learning models compared were PDEODE with AfL, PDEODE with conventional assessment, and direct learning. The population of this research was the students in grade XII Vocational School engineering, health, and agriculture group in Kediri City on academic year of 2015/2016. The hypothesis test used unbalanced two ways analysis of variance. The results of the research were as follow. (1) The learning models of PDEODE with AfL, PDEODE with conventional assessment, and direct learning have an equal learning achievement in mathematics; (2) The mathematics learning achievement of students with auditory learning style was better than students with visual and kinesthetic learning style; the mathematics learning achievement of students with visual and kinesthetic learning styles have an equal learning achievement in mathematics; (3) In each learning style, the students who taught by PDEODE with AfL, PDEODE with conventional assessment, and direct learning have an equal learning achievement in mathematics; and (4) In each learning model, the students with visual, auditory, and kinesthetic learning styles have an equal learning achievement in mathematics.Keywords: Predict Discuss Explain Observe Discuss Explain (PDEODE), Assessment for Learning (AfL), a conventional assessment, and learning style.